Arc erosion behavior of the Al2O3-Cu/(W, Cr) electrical contacts. (1st March 2019) - Zhang, Xiaohui; Zhang, Yi; Tian, Baohong; An, Junchao; Zhao, Zhuan; Volinsky, Alex A.; Liu, Yong; Song, Kexing
Abstract: Al2 O3 -Cu/(25)W(5)Cr and Al2 O3 -Cu/(35)W(5)Cr electrical contact materials were fabricated by vacuum hot-pressing sintering and internal oxidation. The relative density, electrical conductivity, and Brinell hardness were measured. The microstructure was analyzed by scanning electron microscopy and transmission electron microscopy. JF04C electrical contact testing apparatus were used to investigate the electrical contact performance of composites. Arc erosion morphologies were analyzed by scanning electron microscopy and three-dimensional profilometer. The material transfer as well as electrical contact performance were studied during contact make and break operations at 30 V DC with current between 10 and 30 A. It indicates that the nano-Al2 O3 particles pinned dislocations. Material transfers from the cathode to the anode. With the melting, evaporation, and sputtering of Cu during arcing, W particles gather and generate needle-shaped skeletons. Finally, liquid droplets, needle-like structures, craters, and bulges were formed on electrode surfaces after arc erosion. Furthermore, their quantity and morphology are affected by tungsten content. When the content of W in the dispersed copper matrix increases from 25 wt% to 35 wt%, welding force is reduced during the steady operations. In addition, when the arc duration is greater than 8.86 ms, the Al2 O3 -Cu/(35)W(5)Cr contact material has a shorter average arc duration than Al2 O3 -Cu/(25)W(5)Cr at the same arc energy. Graphical abstract: Liquid droplets, needle-like structures, craters, and bulges were formed on the electrode surfaces after arc erosion. Highlights: Vacuum hot-pressing sintering was combined with internal oxidation to fabricate Al2 O3 -Cu/(W, Cr). The mass transfer directions of the two composites are from the cathode to anode. Liquid droplets, needle-like structures, craters and bulges formed on electrode surfaces. The 35 wt% W composite experienced shorter arc duration.